Exploring the Potent Roles of an Internally Translated Truncated Connexin-43 Isoform - Mario Maalouf; Adelaide T. Gaffney; Bridger R. Bell; Robin M. Shaw (Biology)
Connexins are a family of transmembrane proteins that form membrane channels [...]